2002
DOI: 10.1385/abab:98-100:1-9:73
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pretreatments of Corn Stover for Enhancing Enzymatic Digestibility

Abstract: Corn stover, the most abundant agricultural residue in Hungary, is a potential raw material for the production of fuel ethanol as a result of its high content of carbohydrates, but a pretreatment is required for its efficient hydrolysis. In this article, we describe the results using various chemicals such as dilute H2SO4, HCl, and NaOH separately as well as consecutively under relative mild conditions (120 degrees C, 1 h). Pretreatment with 5% H2SO4 or 5% HCl solubilized 85% of the hemicellulose fraction, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 15 publications
4
43
3
2
Order By: Relevance
“…Although large corn stover particles was used in the present study, the glucose and xylose recovery obtained in this study was comparable with most of the alkali pretreatments listed in the table. However, the result of present study was higher than the values reported for alkali (Varga et al, 2002), wet oxidation (Varga et al, 2003), aqueous ammonia soaking pretreatment , lime and alkali pretreatment ). Rodgers et al (2009) achieved higher glucose and xylose yield than the current study.…”
Section: Comparison Of Alkali Soaking-extrusion Results With Other Prcontrasting
confidence: 88%
See 2 more Smart Citations
“…Although large corn stover particles was used in the present study, the glucose and xylose recovery obtained in this study was comparable with most of the alkali pretreatments listed in the table. However, the result of present study was higher than the values reported for alkali (Varga et al, 2002), wet oxidation (Varga et al, 2003), aqueous ammonia soaking pretreatment , lime and alkali pretreatment ). Rodgers et al (2009) achieved higher glucose and xylose yield than the current study.…”
Section: Comparison Of Alkali Soaking-extrusion Results With Other Prcontrasting
confidence: 88%
“…The sugar recovery obtained in the present study was comparable with that of the 88-93% glucose reported for dilute acid pretreatment at 140°C with 0.98% H 2 SO 4 for 40 min (Lloyd & Wyman, 2005), more than 95% glucose and 77% xylose from the dilute acid percolation process at 180°C with 1% acid (w/w) at a flow rate of 10 mL/min for 3 min, followed by N 2 through quenching (Zhu et al, 2004). Varga et al (2002) obtained 95.7% glucose when corn stover was pretreated with 1% NaOH for a day followed by a 60 min autoclaving with 1% H 2 SO 4 . A similar result was reported from compressed hot water pretreatment of corn stover at 200°C with a flow rate of 10 mL/ min for 24 min (Liu & Wyman, 2005).…”
Section: Comparison Of Alkali Soaking-extrusion Results With Other Prsupporting
confidence: 85%
See 1 more Smart Citation
“…Optimal process conditions for enzymatic hydrolysis to high glucose included both high SC and low enzyme loading. This is a remarkable improvement over previous studies done with pretreated corn stover either at low SC (<10 %) or high enzyme loading (>10 FPU, equivalent to 30 mg EP/g glucan) to achieve higher cellulose conversion [5,6,18,19]. By increasing the SC, the glucose yield improved significantly.…”
Section: Influence Of Sc and Enzyme Loading During Enzymatic Hydrolysismentioning
confidence: 63%
“…Gaspar et al (2005) and Wang et al (2010) reported 95 % lignin removal for corn fiber (2,5 % conc.,121 °C, 60 min) and 86 % removal for bermuda grass (3 % conc., 121 °C, 90 min), respectively. The higher lignin removal (95 %) for corn stover reported by Varga et al (2002) might be attributed to the higher NaOH concentration (10 %). In the present study, the NaOH concentration was limited to 2 %.…”
Section: Effects Of Chemical Pretreatment On Lignin Contentmentioning
confidence: 87%